Physico-Chemical Characterization of Lignocellulosic Seed Microfibers - Ritu Pandey; Amarish Dubey; G. Krishna Prasad; A. Arputharaj; A. S. M. Raja; Ragini Dubey; Mukesh Kumar Sinha; Seiko Jose (Journal of Natural Fibers)
The research attempts to report the characterization of eight underexploited seed fibers viz. Adenium, Albizia, Blackboard, Munja, Plume thistle, Poplar, Reed, and Wild sugarcane fiber collected from various trees and shrubs in order to investigate their potential industrial applications. The fibers underwent detailed analysis of their physical properties and chemical components. Fourier transform infrared spectroscopy (FTIR), Thermal gravimetric analysis (TGA), scanning electron microscopy (SEM), and X-ray diffraction (XRD) were employed to determine the chemical, thermal, morphological, and crystalline analysis, respectively. The quantitative estimation of seed fibers by chemical component analysis revealed that the selected seed fibers are rich in cellulose (51.4–67.23%) with 7–25% lignin content. The SEM images depicted that the Munja, Poplar, Plume, and Wild sugarcane fiber are extremely fine with a fiber diameter of less than 10 μm. DTG analysis revealed the correlation between cellulose content and maximum peak temperature of decomposition of the fibers. Except for Adenium and Poplar fibers, all the fibers showed a crystalline index of more than 50%. Comprehensively, the selected seed fibers are comparable to cotton in fineness, density, moisture, and wax content. Gleaming whiteness of poplar fiber is comparable to cotton.